2011
DOI: 10.1186/1471-2148-11-84
|View full text |Cite
|
Sign up to set email alerts
|

An expanded phylogeny of social amoebas (Dictyostelia) shows increasing diversity and new morphological patterns

Abstract: BackgroundSocial Amoebae or Dictyostelia are eukaryotic microbes with a unique life cycle consisting of both uni- and multicellular stages. They have long fascinated molecular, developmental and evolutionary biologists, and Dictyostelium discoideum is now one of the most widely studied eukaryotic microbial models. The first molecular phylogeny of Dictyostelia included most of the species known at the time and suggested an extremely deep taxon with a molecular depth roughly equivalent to Metazoa. The group was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…This is also in agreement with previous studies that found a large undetected diversity within this lineage, and highlights the importance of unraveling it to understand its evolution (Romeralo et al, 2011;Fiz-Palacios et al, 2013;Tekle et al, 2016;Kang et al, 2017).…”
Section: Eukaryotic Diversity In Paraná River Is Similar To Other Fresupporting
confidence: 82%
“…This is also in agreement with previous studies that found a large undetected diversity within this lineage, and highlights the importance of unraveling it to understand its evolution (Romeralo et al, 2011;Fiz-Palacios et al, 2013;Tekle et al, 2016;Kang et al, 2017).…”
Section: Eukaryotic Diversity In Paraná River Is Similar To Other Fresupporting
confidence: 82%
“…Just like groups 1 and 2 in branch I, which are sister clades that evolved independently, groups 3 and 4 are sister clades in branch II, but with Pvio, one of six taxa in the "violaceum" complex [12] occupying a basal position to group 4. Group 4 taxa display major phenotypic innovations, such as two more cell types, cell-type proportioning, extensive slug migration and enhanced fruiting body robustness, which are not yet evident in the “violaceum” complex [18, 20].…”
Section: Discussionmentioning
confidence: 99%
“…The latter was improved by sequencing of the less conserved internal transcribed spacer (ITS) regions between the ribosomal RNAs [11]. Further expansion of the phylogeny with 47 new taxa indicated that the intermediate species may actually represent additional minor groups, which were named the violaceum, polycephalum and polycarpum complexes [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Here, D. discoideum, Dictyostelium citrinum, Dictyostelium intermedium, and Dictyostelium firmibasis have retained only FtsZ whereas their sister taxon D. purpureum and the more basal taxa P. pallidum, Polysphondylium violaceum, and A. subglobosum have additionally maintained all three Min proteins. Meanwhile, the yet more distantly related Dictyostelium fasciculatum (72,73) seems to have independently lost the Min proteins and, like D. discoideum, only possesses FtsZ. This overall pattern raises the question of why Min proteins were retained in some taxa, yet lost in others.…”
Section: Resultsmentioning
confidence: 90%